FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PADA PT. PEGADAIAN (PERSERO) KANWIL I MEDAN - Silky, WANDILA (Jurnal El Rayyan: Jurnal Perbankan Syariah, 2022)
This study aims to analyze the effect of trust on service quality, the effect of understanding on service quality and the influence of facilities on service quality. The research method is a scientific way to obtain data with certain purposes and uses. Based on this, there are four keys that need to be considered, namely, scientific method, data, purpose and use. This study uses the type of research method that the author uses is quantitative. From the results of tests carried out on the H1 hypothesis test, it has been proven that there is a significant influence between the Trust variable on service quality in inputting all data and some customer needs. it can be concluded that in this study, the higher the customer trust, the higher the quality of service at PT. Pegadaian Kanwi I Medan. and some customer needs. From the results of tests carried out on the H3 hypothesis test, it has been proven that there is a negative but significant effect between the Facility variables on service quality. Facilities provided by the company to support the comfort and needs of the company. Trust has a positive and significant effect on Service Quality at PT. Pegadaian Kanwil I Medan. Understanding has no positive and insignificant effect on service quality at PT. Pegadaian Kanwil I Medan..Facilities have a negative and significant effect on service quality at PT.Pegadaian Kanwil I Medan.